Assessing the efficiency of specialty contractors in the construction industry using DEA and Tobit regression - Dae-Woon Jeong; Kyung-Rai Kim; Sungjoo Hwang; JuHyeong Ryu; Byungjoo Choi (Journal of Asian Architecture and Building Engineering)
This study analyzed the efficiency of specialty contractors, a sector often overlooked in existing construction efficiency research, and identified factors influencing their efficiency. Data were collected from 347 Korean specialty contractors from 2017 to 2022. Efficiency was assessed using data envelopment analysis (DEA) to understand changes in efficiency scores across different types of specialty contractors (labor, material, equipment-oriented, and combination). Additionally, Tobit regression was conducted to identify the firm characteristics affecting efficiency. The efficiency of the specialty construction industry exhibited a gradual increase from 2017 to 2020, a rapid decline in 2021 due to the coronavirus pandemic, and a recovery in 2022. Significant determinants of efficiency for all specialty construction firms included firm age, labor cost per employee, sales per employee, equity ratio, debt ratio, and total capital turnover. These results contribute to elucidating specialty contractors’ efficiency and supporting the development of corporate strategies aimed at enhancing their efficiency.